The Role of “Ana’dara Kallolo” as Tourism Ambassador in Promoting Tourism Potential in Soppeng Regency - Vera Rahayu; Muhammad Basri D; Abdollah Abdollah (Tamaddun Life, 2022)
The Soppeng regency required a tourism ambassador to market the region as a tourist information hub. The objectives of the study were to determine the role of Ana'dara Kallolo as a tourism ambassador in promoting tourist attractions and to identify the elements that supported and hindered Ana'dara Kallolo's efforts to promote tourism in Soppeng regency. Based on the foregoing promotions, it became necessary to define the communication strategy employed by Ana'dara Kallolo to promote the programs of tourist attractions. The research employed a qualitative approach to delve more deeply into the subject to be watched closely. Ana'dara Kallolo had important roles as the actors of the activity, as a tourism information centre, and as the Soppeng regency tourism ambassador, according to the findings of the study. The supporting factors indicated a high level of public interest in tourism destination areas in that regency, while the inhibiting factor was the lack of community resources when tourism promotion was conducted. It was determined that the public had recognized Ana'dara Kallolo's information regarding tourism in Soppeng regency as accurate; thus, the barriers to engaging in socializations or other activities must be eliminated by significantly improving human resources. The purpose of the study's execution was to gain the strategy for completing a variety of tasks and to carry out the scheduled activities.